Review: The Multilingual Origins of Standard English. By Laura Wright (ed.). De Gruyter Mouton, 2020. Pp. xi + 534 + 114 b/w illustrations, 84 b/w tables. - Rogos-Hebda, Justyna (Studia Anglica Posnaniensia, 2021)
Review: The Multilingual Origins of Standard English. By Laura Wright (ed.). De Gruyter Mouton, 2020. Pp. xi + 534 + 114 b/w illustrations, 84 b/w tables